URGENSI DIGITAL MARKETING PADA UMKM MENURUT PERSPEKTIF EKONOMI ISLAM (STUDI KASUS UMKM KELURAHAN BABAKAN) - Sahar, Sahar; Laili Hurriati; Muhammad Habibullah Aminy; Lale Ajeng Khalifatun Wardani; Karunia Ema Putri (Jurnal Kompetitif : Media Informasi Ekonomi Pembangunan, Manajemen dan Akuntansi, 2024)
This study aims to describe the digital marketing strategy used by UMKM actors in Babakan Village in maintaining and increasing their business profits in accordance with the perspective of Islamic Economics. This study uses a qualitative descriptive approach. Data collection methods are Observation, unstructured interviews, Documentation and Case Studies. Data analysis techniques used in this study are data reduction (Data Reduction), data presentation (Data Display), Verification. The results of this study indicate that the digital marketing strategy carried out by UMKM actors in Babakan Village is in the form of marketing through social media. The impact of digital marketing in increasing income is very significant, in addition to other positive impacts, namely the creation of wider marketing channels and increasing popularity, reducing advertising costs. Digital marketing is very helpful for UMKM in running their business. With digital marketing, UMKM can promote their business more easily and quickly reach consumers more widely.